The Dinner Party : Judy Chicago and the Power of Popular Feminism, 1970-2007 - Gerhard, Jane F. (Since 1970., 2013)
Judy Chicago's monumental art installation The Dinner Party was an immediate sensation when it debuted in 1979, and today it is considered the most popular work of art to emerge from the second-wave feminist movement. The author examines the piece's popularity to understand how ideas about feminism migrated from activist and intellectual circles into the American mainstream in the last three decades of the twentieth century. More than most social movements, feminism was transmitted and understood through culture-art installations, Ms. Magazine, All in the Family, and thousands of other cultural artifacts. But the phenomenon of cultural feminism came under extraordinary criticism in the late 1970s and 1980s. The author analyzes these divisions over whether cultural feminism was sufficiently activist in light of the shifting line separating liberalism from radicalism in post-1970s America.